The causes of repeated appeals to cardiac clinic of patients with ischemic heart disease with coronary bypass surgery history - S. M. Fanta; L. O. Nevmerzhytsky; Y. O. Lebedieva; J. Q. Jafarov; S. P. Panchenko; K. V. Rudenko; V. V. Lazoryshynetz (Ukrainian Journal of Cardiovascular Surgery, 2016)
In study was investigated the causes of repeated appeals of 250 patients with ischemic heart disease (IHD) from a full array of treated patients in the period from 01.01.2005 to 31.12.2014 years, which was performed coronary artery bypass surgery (CABG). In connection with recurrence of angina symptoms (RA) in these patients was carried out of complex re-examination including coronary and grafts angiography in SI «Amosov National Institute of Cardiovascular Surgery NAMS of Ukraine».